О жизни, учениях и изречениях знаменитых философов - Диоген Лаэртский (ФН: Философское наследие, 1986)
Экземпляры: (20200313) / Инвентарный номер: 11582 / Сис.шифр: 87.3 / Авт.знак: Д46 / ББК: 87.3(0)321